New Guidelines for Severe Community-acquired Pneumonia - Calabretta, Davide; Martìn-Loeches, Ignacio; Torres, Antoni (Seminars in Respiratory and Critical Care Medicine, 2024)
In 2023, the new European guidelines on severe community-acquired pneumonia, providing clinical practice recommendations for the management of this life-threatening infection, characterized by a high burden of mortality, morbidity, and costs for the society. This review article aims to summarize the principal evidence related to eight different questions covered in the guidelines, by also highlighting the future perspectives for research activity.
Keywords: severe community-acquired pneumonia; acute respiratory failure; empiric antibiotic therapy; viral community-acquired pneumonia; corticosteroid therapy